Sol-Gel Method Recent Advances - Pal Singh, Jitendra; Shankar Acharya, Shakti; Kumar, Sudhanshu; Kumar Dixit, Shiv (IntechOpen, 2023)
Synthesizing materials with specific dimensions and properties via a cost-effective approach has long been a major concern among researchers. As such, much research has focused on improving existing synthesis methods or developing new ones. Among the various existing methods, the sol-gel process has been used to synthesize materials for around 100 years. It has recently gained popularity with the evolution of nanoscience and nanotechnology, as it plays a vital role in growing different types of nanostructures, including nanoparticles, thin films, nanotubes, nanorods, nanowalls, and more. The sol-gel process has proven to be a cost-effective, reliable, and reproducible method. This book provides a comprehensive overview of the sol-gel process. It is organized into three sections on the basics and fundamentals of the process, the synthesis of selected materials using the sol-gel method, and the applications of these created materials.